Unorthodox compositional trends in columbite-group minerals from the Animikie Red Ace pegmatite, Wisconsin, USA - Falster,A.U.; Simmons,W.B.; Webber,K.L. (Journal of the Czech Geological Society, 2001)
The 1.8 Ga Penokean age Animikie Red Ace pegmatite in Florence County, Wisconsin, is an example of an extremely fractionated granitic pegmatite system. The dike strikes in a northerly direction and dips at about 68 ° to the west. The pegmatite is strongly zoned with a thin border zone, a rubellite-bearing wall zone, 3 intermediate zones, a core margin, a core zone and several aplite and replacement units. The mineralogy is typical for a highly fractionated pegmatite; it includes Mn- and Ta-rich columbite-tantalite species, spodumene, lepidolite, elbaite, and several exotic minerals such as rhodizite, tantite, wodginite, and hambergite. Members of the columbite-tantalite group are geochemically evolved, with high Mn and Ta abundances in these minerals from the wall zone and the middle intermediate zone. Columbite-tantalite minerals from the other zones are still evolved, though not as highly as those from the wall zone and the middle intermediate zone. In general, there is a decrease in the value of Ta/(Ta+Nb) ratio from the wall zone to the core zone, which is the opposite of what is normally observed in highly evolved pegmatites. The high fractionation trends in the wall zone suggest that the pegmatite magma may have been derived from an already geochemically evolved, much larger pegmatite body at depth.
Keywords: Animikie Red Ace pegmatite; Hoskin Lake granite; Penokean; LCT-type pegmatite; columbite-group minerals